Treatment of epilepsy associated with primary and metastatic brain tumors - A V. Lebedeva; S. G. Burd; P. N. Vlasov; N. A. Ermolenko; I. A. Zhidkova; S. K. Zyryanov; I. Yu. Kovaleva; D. R. Naskhletashvili; N. Yu. Perunova; I. G. Rudakova; R. K. Shikhkerimov; M. A. Yamin (Эпилепсия и пароксизмальные состояния, 2021)
There is a number of unsolved issues in management of epilepsy associated with primary and metastatic brain tumors (BTs). In particular, no consensus approaches to treatment of patients with epilepsy associated with BTs have been proposed regarding use of current anti-epileptic drugs (AEDs). The review presents the relevant data on epidemiology, features of clinically manifested epilepsy at varying stages of BTs, aspects of drug-drug interaction between AEDs and anti-tumor agents, AED-related effects on cognitive functions as well as quality of life in patients with epilepsy associated with BTs. Levetiracetam and valproic acid comprise the first-line drugs for treating seizures in patients with BTs. It is unreasonable to use AEDs acting as hepatic microsomal enzyme inducers for therapy of epileptic seizures in BTs, because it may decrease efficacy of chemotherapy agents and glucocorticoids along with elevated rate of side effects. Perampanel acting as a selective noncompetitive AMPA receptor antagonist, may be one of the drugs of choice for the adjunctive therapy of epileptic seizures associated with BTs.